A giant groin lipoma mimicking an inguinal hernia: a case report - Mehmet Eren Yuksel; Funda Tamer; Esra Oz (Our Dermatology Online, 2019)
An inguinal hernia repair operation is a common procedure in general surgery. However, several other conditions such as inguinal lymphadenopathy, groin lipoma, spermatic-cord lipoma and sarcoma may have similar clinical findings with inguinal hernia. Preoperative diagnosis is crucial to make the appropriate treatment plan. An accurate preoperative diagnosis prevents both unnecessary operations and surgical complications. Radiological imaging techniques such as ultrasonography, computed tomography and magnetic resonance imaging should be considered in the differential diagnosis of inguinal masses. Hereby, we present a 41-year-old Caucasian male patient with a giant lipoma in the right groin which mimicked an inguinal hernia. Preoperative ultrasound imaging helped us to make an initial diagnosis of lipoma which was subsequently confirmed by histopathological examination.